A Reductive Benzylation for Benzenes Using Aroyl Chlorides and Triethylsilane Catalyzed by Aluminosilicate-Stabilized Silyl Cations on Montmorillonite - Tanaka, Yoshiki; Shibata, Shintaro; Hashimoto, Kimiko; Masui, Yoichi; Onaka, Makoto (Synlett, 2022)
We discovered that the aluminosilicate-stabilized silyl cations, which were created from a solid-acid catalyst, the proton-exchanged montmorillonite, and Et3SiH, efficiently promoted the reductive benzylation of benzenes with aromatic carboxylic acid chlorides and Et3SiH in one pot.
Keywords: montmorillonite aluminosilicate-stabilized silyl cations; proton-exchanged montmorillonite; benzoyl chlorides; Et3SiH; benzylation of benzenes; one-pot reaction